Analysis of the Influence of Online Brand Attribute, Brand Trust, and Brand Recognition of Somethinc Skincare Products on Purchase Intention in Indonesia - Jolie, Cellica; Panjaya, Ryan Putra (Technology, Business and Entrepreneurship, 2024)
The purpose of this study is to determine the effect of brand attribute, brand trust, brand recognition of Somethinc skin care products on purchase intention in Indonesia. conducted by distributing questionnaires to customers of Somethinc products in Indonesia. The sample obtained was 52 respondents. The method of determining the sample using convenience sampling method. Based on the test results, it can be concluded that Brand Attribute and have a significant impact on customer purchase intention, while brand trust has a Trust has an insignificant effect on customer purchase intention. Based on the research conducted, it has implications that purchase intention is more influenced by Brand Attribute and Brand Recognition, as a result, brands need to focus more on Improve the brand attribute and brand recognition they already have. This research helps Somethinc companies to find out the influence of Online Brand Attribute, Brand Trust and Brand Recognition on the Purchase Intention of Somethinc companies.